2011
DOI: 10.1530/erc-11-0211
|View full text |Cite
|
Sign up to set email alerts
|

RSUME is implicated in HIF-1-induced VEGF-A production in pituitary tumour cells

Abstract: The recently cloned small RWD-domain containing protein RSUME was shown to increase protein levels of hypoxia-inducible factor-1a (HIF-1a). The latter is the oxygen-regulated subunit of HIF-1, the most important transcription factor of the cellular adaptive processes to hypoxic conditions. It is also a major regulator of vascular endothelial growth factor-A (VEGF-A), which is critically involved in the complex process of tumour neovascularisation. In this study, the expression and role of RSUME in pituitary tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 39 publications
1
51
0
Order By: Relevance
“…Moreover, expression of HIF1 can be upregulated by such receptor-mediated factors as growth factors and cytokines and such circulatory factors as PDGF and EGF, besides hypoxia [39,40]. Overexpression of HIF1 occurs in most common human cancers and their metastases [19]. In tumor cells, HIF1 has been proved to promote tumor migration, invasion, and heterotrophic colonization by mediation of SDF-1/ CXCR4, MMP-9, and PTHrP [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, expression of HIF1 can be upregulated by such receptor-mediated factors as growth factors and cytokines and such circulatory factors as PDGF and EGF, besides hypoxia [39,40]. Overexpression of HIF1 occurs in most common human cancers and their metastases [19]. In tumor cells, HIF1 has been proved to promote tumor migration, invasion, and heterotrophic colonization by mediation of SDF-1/ CXCR4, MMP-9, and PTHrP [10].…”
Section: Discussionmentioning
confidence: 99%
“…HIF1 functions as a factor which promotes the transcription of over 40 downstream proteins essential to survival in hypoxia. Interestingly, vascular endothelial growth factor, the well-acknowledged stimulator of tumor angiogenesis, is one of the downstream proteins regulated by HIF1 [19].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…It has been shown that RSUME could stabilize HIF-1 and thus enhance VEGF-A secretion. Therefore, the knock-down of RSUME was associated with reduced production of HIF-1 and VEGF-A in pituitary tumors in vitro and in vivo 81 . Whether USP8 has similar HIF-1–stabilizing properties and thus influences angiogenic growth factor production in corticotroph tumors needs to be clarified.…”
Section: Progression Of Corticotroph Adenomasmentioning
confidence: 94%
“…As the previously mentioned USP8 protein interferes with HIF-1α deubiquitination processes 25, 79 , it would be interesting to study whether HIF-1 levels are different in corticotropinomas with and without mutated USP8 and whether corticotropinoma vascularization might be affected as in the case of the product of the RWWD3 gene, RWD-domain-containing sumoylation enhancer (RSUME) 80 . The latter is upregulated under hypoxia and overexpressed in pituitary tumors, including corticotropinomas 81 . It has been shown that RSUME could stabilize HIF-1 and thus enhance VEGF-A secretion.…”
Section: Progression Of Corticotroph Adenomasmentioning
confidence: 99%
“…Primary human pituitary adenoma cultures were transfected [71], with 100mM siRNA against human IL-6 (5′-CCCAGGAGAAGAUUCCAAATT-3′) or unspecific siRNA, or with BLOCK-it. After electroporation (using a GenePulser from Bio-Rad, Hercules, California, USA) cells were platted, 72 h after, SA-β-staining was performed.…”
Section: Methodsmentioning
confidence: 99%